Determination of the safety of glycopeptides lactic acid bacteria in laboratory animals - O. V. Sofronova; L. L. Polyakova; A. N. Ovcharova (Фармакокинетика и Фармакодинамика)
The study of acute toxicity and allergenity glycopeptides lactic acid bacteria in mice and rabbits. At the present level of physical, chemical and biological pollution of the environment, domestic and farm animals in no less, if not more than people, suffer from secondary induced immunodeficiency - an imbalance in the normal functioning of the immune system. This leads to a significant reduction in the overall resistance of the animal to various diseases of a viral and bacterial nature. The normal functioning of the animal's immune system can be restored with the help of immunomodulators, the active principle of which is the glycopeptide synthesized from natural components - a universal structural fragment of the lactic acid bacteria cell membrane that interacts with the immune system of the animal organism.